From seminar to practice: Learning to teach using corpus-based methods - Grommes, Patrick; Stulen, Anastasiia (Kalbotyra, 2025)
Implementing the idea of data-driven learning (DDL) in German as a foreign language (DaF) in a way that works in practice requires both teachers’ willingness to engage in further training in corpus linguistics and students’ motivation to participate, as both groups often express skepticism toward this approach. This article outlines three phases of corpus identification and implementation in DaF and draws on two seminars at the University of Hamburg that focused on developing corpus-based teaching approaches for DaF students abroad. Findings from the seminars, together with insights from the literature on DDL in DaF, are used to formulate criteria for reflecting on a corpus-based DaF course. Using a learning unit on the causal connectors denn ʻbecauseʼ, weil ʻbecauseʼ, and da ʻbecauseʼ, which was developed during the second seminar at the University of Hamburg and tested at the Vilnius University, a specific teaching situation is analysed and discussed. The evaluation of the learning unit shows that the development of corpus-based language teaching requires a gradual and systematic process. Continuous training and professional development are essential to better prepare teachers for these methods and to enhance their acceptance in practice.Die Umsetzung des Konzepts des datengestützten Lernens (DDL) im Fach Deutsch als Fremdsprache (DaF) in einer praxisorientierten Weise erfordert sowohl die Bereitschaft der Lehrkräfte, sich in Korpuslinguistik weiterzubilden, als auch die Motivation der Lernenden zur Teilnahme, da beide Gruppen diesem Ansatz oft skeptisch gegenüberstehen. Dieser Artikel skizziert drei Phasen der Korpusidentifizierung und -implementierung in DaF und stützt sich auf zwei Seminare an der Universität Hamburg, die sich mit der Entwicklung korpusbasierter Lehransätze für DaF-Lernende im Ausland befassten. Die Ergebnisse der Seminare werden zusammen mit Erkenntnissen aus der Literatur zum DDL im DaF herangezogen, um Kriterien für die Reflexion über einen korpusbasierten DaF-Kurs zu formulieren. Anhand einer Lerneinheit zu den kausalen Konnektoren denn, weil und da, die während des zweiten Seminars an der Universität Hamburg entwickelt und an der Universität Vilnius getestet wurde, wird eine konkrete Unterrichtssituation analysiert und diskutiert. Die Auswertung der Lerneinheit zeigt, dass die Entwicklung eines korpusbasierten Sprachunterrichts einen schrittweisen und systematischen Prozess erfordert. Kontinuierliche Fortbildung und berufliche Weiterentwicklung sind unerlässlich, um Lehrkräfte besser auf diese Methoden vorzubereiten und ihre Akzeptanz in der Praxis zu verbessern.
Keywords: German as a foreign language; data-driven learning; corpus linguistics; teaching German as a foreign language; DWDS; KWiC